Beta-glucan's varying structure characteristics modulate survival and immune-related genes expression from Vibrio harveyi-infected Artemia franciscana in gnotobiotic conditions. Issue 102 (July 2020) - Han, Biao; Baruah, Kartik; Nguyen, Dung Viet; Williams, David L.; Devriendt, Bert; Cox, Eric; Bossier, Peter
Abstract: β-Glucans have long been used as an immunostimulant in aquaculture. However, the relationship of its structure to its immunomodulatory properties are poorly understood. In this study, the particle size and chemical structure of β-glucans extracted from wild-type strain of baker's yeast ( Saccharomyces cerevisiae ) and its null-mutant yeasts Gas1 were characterised. Using Sigma β-glucan as a reference, the immunomodulatory properties of these polysaccharides in the germ-free Artemia franciscana model system in the presence of Vibrio harveyi bacterial challenge were investigated. The survival of the A. franciscana nauplii, upon challenge with V. harveyi, was significantly higher in all three glucan-treated groups compared to the control. The glucan Gas1 with a lower degree of branching and shorter side chain length had the most prominent V. harveyi -protective effects. The particle size did not affect the nauplii survival when challenged with V. harveyi . Results also showed that the salutary effect of the tested glucans was associated with the upregulation of innate immune genes such as lipopolysaccharide and β-1, 3-glucan-binding protein ( lgbp ), high mobility group box protein ( hmgb ), and prophenoloxidase ( proPO ). Interestingly, the up-regulation of superoxidase dismutase ( sod ) and glutathione-s-transferase ( gst ) was only observed in Gas1 treated group, indicating that Gas1 could function to induce higher reactive oxygen species and stronger immunomodulatory function in A. franciscana, and therefore higher survival rate. The expression of heat shock protein 70 ( hsp70 ), peroxinectin ( pxn ), and down syndrome cell adhesion molecule ( dscam ) remain unaltered in response to glucan treatment. Taken together, this study provides insights into the structure-function relationship of β-glucan and the results confirmed that β-glucan can be an effective immunostimulant in aquaculture, especially the Gas1 glucan. Highlights: The structure of β-glucan influences their bioactivity, and the Gas1 glucan was shown to be more effective. The Gas1 glucan with a lower degree of branching and shorter side chain length prone to enhance the oxidative burst activity. Homologs of several immune-related genes were firstly identified in the Artemia franciscana transcriptome.